Recognition and legitimacy of transitional governments under international law a case of Libya - Hamed Hashemi Sougheh; Rohaida Nordin (Penerbit Universiti Kebangsaan Malaysia, 2019)
The National Transitional Council of Libya (Libyan NTC), a form of transitional government, emerged on the political scene of Libya after the eruption of internal armed conflict in Libya, and played a major role in the building of the State during the transition. Despite that, there is ongoing debate on the recognition of any transitional government in general and the Libyan NTC specifically, by the international community. In some cases, the international community will provide premature recognition to transitional government to prevent the situation of a failed State. The other problem with transitional governments is that the scope of their responsibility is vague with regard to the commission of mass violations of international humanitarian law and human rights law in the territories under their jurisdiction. Within this specific context, this book discusses the legitimacy and legality of the recognition of the Libyan NTC which claimed to be controversial.